The Epidemiology of Literacy Difficulties (Focusing on Children with Speech and Language Impairment) - Leitao, Suze (2003)
Speech and language impairment in preschool children is frequently a precursor of language and literacy difficulties that persist throughout childhood into adolescence and beyond. For the majority, the surface level symptoms of speech and language impairment change over time, but the underlying difficulties persist with negative impact on both spoken and written language development. Children with literacy difficulties are a heterogeneous group. A classification of reading difficulties is presented which is based on a simple model of reading (reading comprehension can be seen as the product of skills in decoding and listening comprehension). Three distinct subgroups of individuals with reading difficulties arise; those with dyslexia, those with a specific comprehension deficit and those with a broader based reading disability (language-based). This paper aims to describe each of these three groups, and present worldwide and local prevalence data (where available).